MiRNAs and their potential for use against cancer and other diseases. (October 2007) - Tili, Esmerina; Michaille, Jean-Jacques; Gandhi, Varsha; Plunkett, William; Sampath, Deepa; Calin, George Adrian
MiRNAs are 19––24 nucleotide long noncoding RNAs found in almost all genetically dissected species, including viruses, plants, nematodes, flies, fish, mice and humans. Rapid advances have been made in understanding their physiological functions, while abnormal patterns of miRNA expression have been found in many disease states, most notably human cancer. It is now clear that miRNAs represent a class of genes with a great potential for use in diagnosis, prognosis and therapy. In this review we will focus on the discoveries that elucidate their crucial role in mammalian diseases, particularly in cancer, and propose that miRNA-based gene therapy might become the potential technology of choice in a wide range of human diseases including cancer.